Impact of the COVID-19 pandemic and work-related stress in Umbrian healthcare workers during Phase 1 in Italy - Paolocci, Giulia; Bussotti, Pietro; Pompili, Camilla; Muzi, Giacomo; Gambelunghe, Angela; Dell'Omo, Marco; Murgia, Nicola; Folletti, Ilenia (La Medicina del Lavoro, 2021)
Background: Depression, anxiety, psychological distress, and poor sleep quality increased in healthcare workers (HCWs) during the COVID-19 pandemic. The aim of the study was to assess levels of psychological distress in Umbrian HCWs during the COVID-19 Phase 1 lockdown along with exploring the relationship between sociodemographic/occupational factors. Methods: Data on sociodemographic and occupational characteristics, change of job description, economic losses and emergency involvement and SARS-CoV2 infections in the workplace were collected using an anonymous online survey sent by healthcare professional associations. Data concerning psychological healthcare distress, were collected anonymously using BIAS 20 (stress balance) and Depression Anxiety Stress Scales (DASS-21). Results: One thousand and one healthcare workers responded to the questionnaire. Biological risk at work was perceived by all HCWs, less so from psychologists and more so from those working in hospitals. Stress symptoms (DASS21 >14) were associated with a younger age group (OR 0.98; 95% CI 0.97-0.99) and less work experience (OR 0.98; 95% CI 0.96-0.99). Younger age was also associated with anxiety symptoms (DASS 21 >7) (OR 0.98; 95% CI 0.97-0.99), as well as graduate/post graduate education level (OR 2.04; 95% CI 1.14-3.63). Working as an independent contractor was a risk factor for high stress health impact (OR 2.00; CI 1.40-2.86) and stress (OR 1.87; CI 1.20-2.92), anxiety (OR 1.89; CI 1.22-2.92) and depression (OR 1.57; CI 1.10-2.22) symptoms. Conclusions: Our study showed a possible relationship between healthcare type of employment and distress symptoms during Covid19 pandemic phase 1. Results of our study should be confirmed in other Italian healthcare settings and could serve as a preliminarily baseline for multidisciplinary Italian collaboration.